On the Comparison of Impulsivity between HIV Positive Persons, Drug-Dependent Persons, and Healthy Counterparts - M Nikoogoftar; Sh Anaghcheh (Drug Control Headquarters, Research and Education Office, 2015)
Objective: This study was an attempt to compare impulsive decision-making between AIDS sufferers, people suffering substance abuse, and nonclinical populations. Method: This was a causal-comparative study which was conducted within the six months of 2011. In this study, 30 AIDS sufferers, 30 drug abusers, and 30 healthy subjects from nonclinical population in the 15-67 age range were selected through convenience sampling. The selected participants were matched in terms of age, education, and gender. Barratt Impulsiveness Scale (1997) were administered to the three groups. Results: The results showed that there was a significant difference among the three groups in impulsivity subscales. Conclusion: The results showed that there existed some degree of deficiency in decision-making processes in AIDS sufferers and drug dependent persons. It may be rooted in a number of personality traits neurological damage drug use the insufficiency of appropriate training in life skills, problem-solving, and decision-making the availability of emotions at paly and personal and cultural thoughts and beliefs around protective behaviors in sexual relationships.